Performance diagnosis by mathematical simulation in table tennis - Hohmann, A.; Zhang, H. (Journal of Sports Sciences, 2006)
The purpose of this paper is to show how the concept of performance diagnosis by mathematical simulation (Lames 1991; Perl, 1993) can be transferred to table tennis. According to that concept, the series of the interactive game actions (e.g. serve, return, offense, defense, and so on) can be described by means of a statistical transition matrix between the different states of action. After the series of the game actions is modeled by a Markov chain, the relevance of each game action for the final win or loss of the game can be simulated.